Use of laser therapy as a treatment for trigeminal neuralgia: Literature review (Research, Society and Development, 2022)
Trigeminal neuralgia is known to be intense pain and one of the most common neurological disorders. This pain is sometimes accompanied by facial spasms, also known as “painful tics”. The variable forms of treatment reported in the literature range from clinical drug therapies to minimally invasive procedures such as the use of laser therapy, which is currently the most discussed. Therefore, the present study aims to analyze the therapeutic efficacy of the use of laser therapy in patients with trigeminal neuralgia. The research was carried out through a descriptive literature review, based on the literature found in the Scientific Electronic Library Online (SCIELO), Google Scholar and Pubmed, between 2013 and 2021 in Portuguese and English. In this perspective, it is concluded that the results of treatment with the use of laser therapy are satisfactory, however, further studies are needed to precisely establish the appropriate technique to use laser therapy.